Assessment of Liver Function With MRI: Where Do We Stand? - Río Bártulos, Carolina; Senk, Karin; Schumacher, Mona; Plath, Jan; Kaiser, Nico; Bade, Ragnar; Woetzel, Jan; Wiggermann, Philipp (Frontiers in Medicine, 2022)
Liver disease and hepatocellular carcinoma (HCC) have become a global health burden. For this reason, determination of liver function plays a central role in the monitoring of patients with chronic liver disease or HCC. Furthermore, assessment of liver function is important, e.g. before surgery to prevent liver failure after hepatectomy or to monitor the course of treatment. Liver function and disease severity are usually assessed clinically based on clinical symptoms, biopsy, and blood parameters. These are rather static tests that reflect the current state of the liver without considering changes in liver function. With the development of liver-specific contrast agents for MRI, noninvasive dynamic determination of liver function based on signal intensity or using T1 relaxometry has become possible. The advantage of this imaging modality is that it provides additional information about vascular structure, anatomy and also on the heterogeneous distribution of liver function. In this review, we summarize and discuss the results published in recent years on this technique. Indeed, recent data show that the T1 reduction rate seems to be the most appropriate value for determining liver function by MRI. Furthermore, attention has been paid to the development of automated tools for image analysis in order to uncover the steps necessary to obtain a complete process flow from image segmentation to image registration to image analysis. In conclusion, the published data show that liver function values obtained from contrast-enhanced MRI images correlate significantly with global liver function parameters, making it possible to obtain both functional and anatomic information with a single modality.